Green & sustainability: upcycled jeans / Nur Shamirah Abd Rahim, Najua Tulos and Nasa'ie Zainuddin - Abd Rahim, Nur Shamirah; Tulos, Najua; Zainuddin, Nasa'ie (2020)
This research study aims to upcycle the discarded jeans into other products as well as to utilise clothing waste in an attempt to help minimise environmental pollution. The methodology used in this research consists of the flow of four components, which begins with the collection of used jeans and proceeds to generate an upcycling product. Then, data processing started with a survey and ended with a system of the data analysis method. A sufficient number of jeans were collected and assembled for recycling. The survey was conducted through a questionnaire distribution given out to respondents in order to observe the acceptance of the students towards the developed product. The qualitative approach in data analysis method was used in evaluating the acceptance of the students towards an upcycled product. The data obtained were analysed and discussed critically and brings to the understanding of students' perception, acceptance and willingness to purchase the upcycled product. In conclusion, the acceptance level of the product is positively received, and it has the potential to be commercialised.